Methane conversion to syngas and hydrogen in a dual phase Ce0.8Sm0.2O2-δ-Sr2Fe1.5Mo0.5O5+δ membrane reactor with improved stability. (2nd August 2018) - Liang, Wenyuan; Zhou, Hangyue; Caro, Jürgen; Jiang, Heqing
Abstract: Coupling of partial oxidation of methane (POM) with water dissociation in an oxygen transport membrane is a promising technology for methane utilization. However, cobalt-based membrane materials show poor stability under the above harsh conditions. In this work, a nominal 60 wt % Ce0.8 Sm0.2 O2-δ -40 wt % Sr2 Fe1.5 Mo0.5 O5+δ (CSO-SFMO) dual phase membrane is reported, which was synthesized by using a one-pot EDTA-citric acid complexing method. The phase structure and morphology of the CSO-SFMO membrane were characterized by XRD, SEM and EDXS. It was found that a uniform distribution of CSO phase with a fluorite structure and SFMO phase with a perovskite structure was achieved in the dual phase membrane. The CSO-SFMO membrane exhibited an improved stability compared with cobalt based perovskite Ba0.5 Sr0.5 Co0.8 Fe0.2 O3-δ, (BSCF) membrane under CO2 or reductive gas atmospheres. The oxygen permeation flux of the dual phase membrane was investigated under different oxygen partial pressure gradients: air/He, air/CO2, air/POM, and H2 O/POM. At 950 °C, the oxygen permeation fluxes of the CSO-SFMO membrane under air/POM and H2 O/POM gradients were 2.7 cm 3 (STP) min −1 cm −2 and 0.75 cm 3 (STP) min −1 cm −2, respectively, which were much higher than the oxygen flux of 0.1 cm 3 (STP) min −1 cm −2 under air/He. Moreover, a CO selectivity of 98%, a CH4 conversion of 97% on the POM side and a H2 production of 1.5 cm 3 (STP) min −1 cm −2 on the H2 O splitting side were achieved in CSO-SFMO membrane reactor under the oxygen partial pressure gradient of H2 O/POM, which was steadily run for 100 h before the measurement was intentionally stopped. Graphical abstract: A stable dual phase oxygen transport membrane was developed, which was steadily run for the production of hydrogen on steam side and synthesis gas on methane side. Image 1 Highlights: A dual phase membrane Ce0.8 Sm0.2 O2−δ -Sr2 Fe1.5 Mo0.5 O5+δ (CSO-SFMO) was synthesized. It exhibited an improved stability under CO2 or reductive gas atmospheres. Oxygen fluxes were investigated under air/He (CO2 ), air/POM, and H2 O/POM gradients. The CSO-SFMO membrane was steadily run for 100 h under H2 O/POM conditions.